BioCAS: Biometeorological Climate impact Assessment System for building-scale impact assessment of heat-stress related mortality - Kim, Kyu Rang; Yi, Chaeyeon; Lee, Ji-Sun; Meier, Fred; Jänicke, Britta; Fehrenbach, Ute; Scherer, Dieter (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
An urban climate analysis system for Seoul was combined with biometeorological models for the spatially distributed assessment of heat stress risks. The Biometeorological Climate impact Assessment System (BioCAS) is based on the Climate Analysis Seoul (CAS) workbench which provides urban planners with gridded data relevant for local climate assessment at 25 m and 5 m spatial resolutions. The influence of building morphology and vegetation on mean radiant temperature Tmrt was simulated by the SOLWEIG model. Gridded hourly perceived temperature PT was computed using the Klima-Michel Model for a hot day in 2012. Daily maximum perceived temperature PTmax was then derived from these data and applied to an empirical-statistical model that explains the relationship between PTmax and excess mortality rate rEM in Seoul. The resultant rEM map quantifies the detrimental impact of hot weather at the building scale. Mean (maximum) values of rEM in old and new town areas in an urban re-development site in Seoul were estimated at 2.3 % (50.7 %) and 0 % (8.6 %), respectively, indicating that urban re-development in the new town area has generally resulted in a strong reduction of heat-stress related mortality. The study illustrates that BioCAS can generally be applied for the quantification of the impacts of hot weather on human health for different urban development scenarios. Further improvements are required, particularly to consider indoor climate conditions causing heat stress, as well as socio-economic status and population structure of local residents.